Randomized controlled studies evaluating Topiramate, Botulinum toxin type A, and mABs targeting CGRP in patients with chronic migraine and medication overuse headache: A systematic review and meta-analysis. (April 2023) - Giri, Samita; Tronvik, Erling; Linde, Mattias; Pedersen, Sindre Andre; Hagen, Knut
Background: This systematic review focuses on chronic migraine patients with medication overuse headache using, respectively, topiramate, botulinum toxin type A, and human monoclonal antibodies targeting calcitonin gene-related peptide or its receptor. Methods: A systematic search was conducted in the databases CENTRAL, MEDLINE, Embase and Web of Science until May 2022. We included randomized controlled trials reporting the outcomes of change in monthly headache/migraine days, ≥50% response rates and change in medication overuse status. Studies were excluded if response rates were not reported. Risk of bias assessment was performed using the Cochrane RoB2 tool. The quality of evidence for outcomes across included studies was evaluated according to the five factors outlined in Cochrane GRADE approach. Findings: The initial search resulted in 1599 records. Following screening, 10 studies met our inclusion criteria, while seven studies with sufficient data were included in the meta-analysis. Studies assessing Botulinum toxin type A included 1139 patients and showed a mean reduction in headache frequency by 1.92 days per month compared to placebo (−1.92; 95% CI −2.68 to −1.16). Studies assessing human monoclonal antibodies included 1982 patients, and showed significant positive effect compared to placebo for all measured outcomes. The overall odds ratio for the ≥50% response rate was 2.90 (95% CI, 2.23 to 3.78). No significant difference was observed in the frequency of adverse effect for both Botulinum toxin type A and low dose of human monoclonal antibodies compared to placebo. There is currently insufficient evidence to determine the impact of topiramate in chronic migraine patients with medication overuse headache. Interpretation: Botulinum toxin type A and human monoclonal antibodies targeting calcitonin gene-related peptide receptor were beneficial in reducing monthly migraine days and ≥50% response rate, but uncertainties remained for Botulinum toxin type A regarding response rate. The effect size for human monoclonal antibodies was greater with relatively lower drop-out rate. High-quality randomized trials are required to evaluate the effect of topiramate in chronic migraine patients with medication overuse headache.